Multilevel needs assessment of physical activity, sport, psychological needs, and nutrition in rural children and adults - Greeven, Sarah J.; Medellin, Andrew M.; Watkins, Janette M.; Coble, Cassandra J.; Brunnemer, Julia E.; Fernández Solá, Paola A.; Dutta, Sandeep; Hobson, James M.; Evanovich, Justin M.; Martinez Kercher, Vanessa M.; Kercher, Kyle A. (Frontiers in Public Health, 2023)
Introduction: Physical activity yields significant benefits, yet fewer than 1 in 4 youth meet federal guidelines. Children in rural areas from low socioeconomic (SES) backgrounds face unique physical activity contextual challenges. In line with Stage 0 with the NIH Stage Model for Behavioral Intervention Development, the objective of the present study was to conduct a community-engaged needs assessment survey with middle school children and adults to identify perceptions, barriers, and facilitators of physical activity, sport, psychological needs, and nutrition from a multi-level lens. Methods: A cross-sectional survey data collection was conducted with children (n=39) and adults (n=63) from one middle school community in the Midwestern United States. The child sample was 33% 6th grade; 51% 7th grade and was 49% female. The adult sample was primarily between 30-39 years old (70%) and comprised predominantly of females (85%). Multi-level survey design was guided by the psychological needs mini-theory within self-determination theory and aimed to identify individual perceptions, barriers, and facilitators in line with the unique context of the community. Results: At the individual level, 71.8% of children and 82.2% of the overall sample (children and adults) were interested in new physical activity/sport programming for their school. Likewise, 89.7% of children and 96.8% of adults agree that PA is good for physical health. For basic psychological needs in the overall sample, relatedness was significantly greater than the autonomy and competence subscales. Children’s fruit and vegetable intake were below recommended levels, yet only 43.6% of children were interested in nutritional programming. Conversely, 61.5% indicated interest at increasing leadership skills. At the policy-systems-environmental level, the respondents’ feedback indicated that the condition and availability of equipment are areas in need of improvement to encourage more physical activity. Qualitative responses are presented within for physical activity-related school policy changes. Discussion: Interventions addressing children’s physical activity lack sustainability, scalability, and impact due to limited stakeholder involvement and often neglect early behavioral intervention stages. The present study identified perspectives, barriers, and facilitators of physical activity, sport, psychological needs, and nutrition in a multi-level context and forms the initial campus-community partnership between scientists and community stakeholders.